Synthesis and Characterization of Silver Nanoparticles (AgNPs) using Chemico-physical Methods - Tooba Siddiqui; Mohammad Khalid Zia; Mohammad Muaz; Haseeb Ahsan; Fahim Halim Khan (Universitas Islam Indonesia, 2023)
Silver nanoparticles (AgNPs) have several applications in nanoscience and nanomedicine such as antibacterial, antifungal, anti-inï¬‚ammatory and anti-angiogenic properties. In the present study, the AgNPs were synthesized by the chemical method and characterised using a combination of UV-Visible (UV-Vis) spectrophotometry, Fourier Transform Infra-Red (FTIR) spectroscopy, transmission electron microscopy (TEM) and X-ray diffraction (XRD). The AgNPs were made by chemically reducing AgNO3 with NaBH4 leading to the formation of a characteristic yellowish-brown colour of AgNPs. To investigate the formation, crystalline behavior, and quality of AgNPs powder, XRD measurements were performed.Â The produced AgNPs were found to be spherical, dispersed, and scattered in form and the particle size of the AgNPs formed was about 15 nm and they were crystalline in nature. The interaction of AgNO3 with biomolecules may have numerous applications in nanoscience and nanomedicine.